HealthNav@Info: a personal mobile mapping healthcare system for community accessibility services / Abdul Hakim Zain Rashid, Abdul Rauf Abdul Rasam and Syahir Shamsuddin - Rashid, Abdul Hakim Zain; Abdul Rasam, Abdul Rauf; Shamsuddin, Syahir (Universiti Teknologi MARA, Kedah, 2019)
A systematic healthcare facilities and accessibility system in developing countries are mostly located in urban areas rather than in rural areas, causing inconvenience to low-and-middle-income residents to reach healthcare centres. Therefore, an innovative geo-mapping and mobile applications or HealthNav@Info is developed in this invention towards modernising healthcare systems in Pulau Indah, Malaysia. The framework of geospatial functions and system development life cycle (SLDC) were implemented to create the proposed system. Respondents revealed that majority of the community are displeased with the existing system performances. This inventive healthcare accessibility system has created eminent geospatial modules to intensify the existing system. this personal apps system offers spatial network analyses to assist the local community to find an optimum accessibility to reach ideal healthcare centres. Inclusively, selected local communities also agreed with functions proposed in the system to easily access the healthcare information and accessibility services. HealthNav@Info has practically implemented in the study area, and the system could be applied at other areas especially in rural and low- and middle-income communities.